Memaknai Nilai Spiritualitas dalam Film The Unholy - Riki Bastian; Muchammad Abdul Ghofur; Herru Prasetya Widodo (Lenvari: Journal of Social Science, 2023)
Films can affect social life, lifestyle and morals. One of them is human spirituality. The purpose of this research is to find out how spiritual values ​​are expressed in the film The Unholy. Spiritual values ​​are according to Roland Barthes' semiotic theory which includes denotation, connotation and myth. This research uses descriptive qualitative method and Roland Barthes semiotic analysis method. The subject of research is the film The Unholy which was released on March 31, 2021, produced by Screen Gems and Ghost House Pictures, and directed by Evan Spiliotopoulos. These spiritual values ​​are then analyzed through the signs and symbols found in selected scenes through stills from the film The Unholy. The results showed that, from 7 scenes in The Unholy, based on an analysis based on denotations and connotations in The Unholy, it was found that the spiritual values ​​contained in The Unholy represent loyalty, trust and belief, the ability to find meaning in life, harmony, truth, hope and faith. The value of spirituality is reflected in the attitude, dialogue and facial expressions between the players, as well as the tone of voice displayed by the characters in The Unholy. This research is expected to be useful for many parties, namely the film industry, society and researchers related to spiritual concepts.